2011
DOI: 10.2174/157489211795328495
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Metallothionein for Prognosis and Treatment of Breast Cancer

Abstract: Breast cancer is a disease that has plagued many women globally. The rapid rise in the incidence rate has prompted the rigorous search to understand its etiology and find better management strategies for this disease. Metallothionein (MT) belongs to a family of metal-binding proteins where dysregulated expression of this protein has been observed in invasive breast ductal carcinomas. Since its discovery in equine kidney, functions of MT have extended beyond the initial role of heavy metal detoxification to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Although the key roles of MTs in mediating heavy metal detoxification have been abundantly documented (20), their implication in the control of gene transcription is still unclear. It has been proposed that MT could bind to the p50 subunit of the NF-κB complex, thereby increasing its ability to act as a transcriptional activator (21).…”
Section: Discussionmentioning
confidence: 99%
“…Although the key roles of MTs in mediating heavy metal detoxification have been abundantly documented (20), their implication in the control of gene transcription is still unclear. It has been proposed that MT could bind to the p50 subunit of the NF-κB complex, thereby increasing its ability to act as a transcriptional activator (21).…”
Section: Discussionmentioning
confidence: 99%
“…MTs, because of their roles in tumors, can be targeted for cancer therapy (Lai et al, 2011). Silencing of MT by short interfering RNA (siRNA) was published by Tarapore et al, who used phage Phi29 motor pRNA as a vehicle to carry siRNA specifically targeted to MT-2A mRNA in ovarian cancers (Tarapore et al, 2011), and by Lai et al, who reported that silencing of the MT-2A gene by siRNA induces entosis (a process involving the invasion of one cell into another, and internalized cells are either degraded by lysosomal enzymes or released) in adherent MCF-7 breast cancer cells (Lai et al, 2010).…”
Section: Mts In Cancer Therapymentioning
confidence: 99%
“…This may be the pathological basis of breast cancer [21]. In this study, RT-PCR and western blot methods were used to detect the expressions of the autophagy-related gene, Beclin1, as well as apoptosisrelated genes Bcl-2 and Bax in breast cancer tissues.…”
mentioning
confidence: 99%